Synthesis of CuSCN particles in deep eutectic solvents and its application in the thermal decomposition of ammonium perchlorate. (1st July 2016) - Lv, Shiqi; Sui, Lin; Zeng, Ying; Cheng, Yun; Liu, Chunsheng; Luo, Genxiang
ABSTRACT: CuSCN particles were successfully synthesized by a simple, mild reaction of copper sulfate, copper powder, and potassium thiocyanate at 70°C in deep eutectic solvents (DES). The as-prepared products were characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), and thermogravimetric analysis (TG). The catalytic performance of the CuSCN particles was investigated by TG. It was found that the higher decomposition temperature of ammonium perchlorate (AP) can be decreased by over 100°C via adding a small amount CuSCN particles in AP.